Pengembangan E-Learning Menggunakan Schoology terintegrasi Model Problem Based Learning Pada Materi Daur Ulang Limbah Untuk SMA: (Development of E-Learning Using Integrated Schoology Model Problem Based Learning in Waste Recycling For High School) - Isnaini Chasanah; Evita Anggereini; Ervan Johan Wicaksana (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2023)
This reseach is to develop, determine the feasibility, and determine the assessment of teachers and students on the product being developed. This type of research is the development of research and development (R&D) with the ADDIE model. The test subjects in this study were a biology teacher and a class X MIPA student at SMAN 6 Batanghari. The data analysis technique in this research is quantitative and qualitative data analysis. The results of media validation by media experts were carried out twice, obtained a score percentage of 87.2%